1996
DOI: 10.3109/03009749609082660
|View full text |Cite
|
Sign up to set email alerts
|

The Role of T-lymphocytes and Cytokines in Rheumatoid Arthritis

Abstract: In this review the involvement of T cells, in addition to that of the monocyte/macrophage lineage, in the pathogenesis of rheumatoid arthritis is discussed. The evidence for the pathogenetic importance of T cells is based upon their state of activation in the synovial membrane and the cytokines produced. These cytokines can be detected in synovial fluids as well as in the synovial membrane by both immunohistochemistry and in situ hybridization. However, cytokine production can be detected only in a minor fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…During RA development, proinflammatory cytokines, such as TNF-␣, IL-1␤, INF-␥, and IL-2, play important roles in chronic joint inflammation and the acceleration of pannus formation and in the mediation of cartilage and bone destruction (Smolen et al, 1996;Lü nemann et al, 2002). Therefore, the regulations and/or normalizations of these cytokine levels are probably important from the therapeutic standpoint.…”
Section: Discussionmentioning
confidence: 99%
“…During RA development, proinflammatory cytokines, such as TNF-␣, IL-1␤, INF-␥, and IL-2, play important roles in chronic joint inflammation and the acceleration of pannus formation and in the mediation of cartilage and bone destruction (Smolen et al, 1996;Lü nemann et al, 2002). Therefore, the regulations and/or normalizations of these cytokine levels are probably important from the therapeutic standpoint.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism and pathogenesis of RA have not been fully clarified. RA has traditionally been assumed to be a Th1-type disease (28,29). However, recent studies revealed a new lineage of effector CD4 ϩ T cells characterized by the production of IL-17, and this Th17 lineage plays an essential role in both the development of autoimmune arthritis (30,31) and bone destruction (32).…”
mentioning
confidence: 99%
“…Transduction of NFκB leads to the activation of various genes including those for various pro-inflammatory cytokines and metalloproteinases. The NFκB activating TNF and IL-1 are both important factors in the pathogenesis of joint destruction associated with RA [37][38][39] and leflunomide appears to inhibit TNF and IL-1 mediated signal transduction.…”
Section: In Vitro Studies and Mechanism Of Actionmentioning
confidence: 98%